2011
DOI: 10.1158/1538-7445.am2011-lb-142
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-142: Regulation of MYCN stability by reactive oxygen species in neuroblastoma

Abstract: Neuroblastoma (NB) is the most common extracranial solid tumor in children. Amplification of the MYCN proto-oncogene is associated with older age, rapid tumor progression, and the worst outcome of this disease. As MYCN amplification leads to its over-expression, high-level expression of MYCN is thought to cause an aggressive behavior of MYCN amplified tumors. In fact, the forced reduction of MYCN protein expression by siRNA results in growth suppression and apoptosis of NB cells with MYCN amplification. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We previously demonstrated that FCCP, a known mitochondrial inhibitor, destabilized MYC and MYCN in NB cells and induced a growth suppressive effect ( 7 ). In this study, to investigate whether MIBG, which is also a mitochondrial inhibitor, exhibits a similar effect on MYC/MYCN in NB cells, we examined MYC/MYCN expression in NB cell lines treated with MIBG (10 and 20 μM) for 4 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that FCCP, a known mitochondrial inhibitor, destabilized MYC and MYCN in NB cells and induced a growth suppressive effect ( 7 ). In this study, to investigate whether MIBG, which is also a mitochondrial inhibitor, exhibits a similar effect on MYC/MYCN in NB cells, we examined MYC/MYCN expression in NB cell lines treated with MIBG (10 and 20 μM) for 4 days.…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that MYCN and/or MYC expression are among the major determining factors of NB aggressiveness. Previously, we also found that mitochondrial inhibitors, such as carbonylcyanide p-trifluoromethoxyphenylhydrazone (FCCP), can destabilize MYC/MYCN and suppress the growth of NB cells ( 7 ), suggesting the potential use of mitochondrial inhibitors in the treatment of NB.…”
Section: Introductionmentioning
confidence: 99%